2008
DOI: 10.1073/pnas.0711669105
|View full text |Cite|
|
Sign up to set email alerts
|

Structural plasticity with preserved topology in the postsynaptic protein network

Abstract: The size, shape, and molecular arrangement of the postsynaptic density (PSD) determine the function of excitatory synapses in the brain. Here, we directly measured the internal dynamics of scaffold proteins within single living PSDs, focusing on the principal scaffold protein PSD-95. We found that individual PSDs undergo rapid, continuous changes in morphology driven by the actin cytoskeleton and regulated by synaptic activity. This structural plasticity is accompanied by rapid fluctuations in internal scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 53 publications
9
104
1
Order By: Relevance
“…To this end, the authors performed extended (1 h) time-lapse imaging of synaptic clusters composed of surface AMPARs. As expected from previous studies showing a substantial PSD flexibility (Blanpied et al, 2008), they observed that individual AMPAR clusters exhibit substantial and continuous changes in their morphology. In contrast to the continuously dynamic structure of AMPAR clusters, SEP fluorescence intensity was extremely stable over time.…”
Section: Review Of Kerr and Blanpiedsupporting
confidence: 61%
“…To this end, the authors performed extended (1 h) time-lapse imaging of synaptic clusters composed of surface AMPARs. As expected from previous studies showing a substantial PSD flexibility (Blanpied et al, 2008), they observed that individual AMPAR clusters exhibit substantial and continuous changes in their morphology. In contrast to the continuously dynamic structure of AMPAR clusters, SEP fluorescence intensity was extremely stable over time.…”
Section: Review Of Kerr and Blanpiedsupporting
confidence: 61%
“…The dynamic behavior of PSDs in living neurons in culture and in vivo has been typically visualized by GFP-tagged PSD-95, which localizes specifically in the PSD. This approach revealed that overall PSD structure undergoes continuous remodeling over a timescale of minutes to days (Blanpied et al 2008;Minerbi et al 2009). Within the PSD, however, mixing of existing PSD-95 molecules is relatively limited, suggesting that individual PSD-95 molecules, once integrated, maintain stable positions within the PSD (Blanpied et al 2008).…”
Section: Basal and Activity-dependent Protein Turnover In The Psdmentioning
confidence: 99%
“…The PSD itself undergoes rapid morphology fluctuations in response to synaptic activity, and also widens concomitantly with expansion of the spine head during its maturation (Blanpied et al, 2008).…”
Section: Myosin II In Actin Organization During Dendritic Spine Maturmentioning
confidence: 99%
“…While many molecules that reside in the PSD have been identified, much less is known about the mechanisms that determine its morphology and organization (Peng et al, 2004;Cheng et al, 2006). The PSD is now thought to be dynamic and undergo rapid fluctuations in morphology (Blanpied et al, 2008;Frost et al, 2010b). Several proteins within the PSD scaffold reportedly interact with the actin cytoskeleton (Böckers et al, 2001;Sheng and Hoogenraad, 2007), raising the possibility that actin organization may underlie PSD morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation